In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

Catalytic applications of hydrotalcite and related materials in multi -component reactions: concepts, challenges and future scope - Burange, Anand S.; Gopinath, Chinnakonda S. (Sustainable Chemistry and Pharmacy, 2021)
Hydrotalcites (HTs) are the potential substitute to conventional base catalysts. HTs are useful in efficient syntheses of various heterocycles, such as chromenes, pyrans, pyrazoles, triazoles, using multi-component reactions. This review focuses on the chemistry of HTs and particularly hydrotalcites and related materials in the synthesis of heterocycles. The effects of preparation method and, physico-chemical parameters, such as calcination, molar ratio of metals, role of intercalated ions, surface area, on the catalytic activities are discussed. Along with technical aspects, this review also unlocks various untouched areas in developing sustainable catalyst for syntheses of heterocycles, drugs, etc. for the future.
Keywords: green chemistry; green synthesis; heterocycles; heterogeneous catalysis; hydrotalcite; Metal Oxide

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide

Synthesis of glycolic acid from glyoxal by using hydrotalcite catalyst and kinetic studies - Pandya, Harmitkumar N.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (ChemCatChem, 2025)
In this work, Mg-Al hydrotalcite catalysts with different molar ratios were prepared using the co-precipitation method for the synthesis of glycolic acid (GA) from glyoxal. Various reaction parameters such as catalyst molar ratio, time, temperature, catalyst loading, and catalyst poisoning were studied and optimized for better conversion of glyoxal selectively to glycolic acid. Hydrotalcite catalyst with a 2:1 molar ratio of Mg: Al gives 98% conversion of glyoxal with 96% selectivity of glycolic acid at 100 degrees C temperature, 40% catalyst loading, and water as solvent in 8 h. Different characterization methods were used such as XRD, XPS, SEM-EDX, nitrogen adsorption desorption, and CO2-TPD for hydrotalcite catalyst. A kinetic study was also performed to observe the reaction order and activation energy required for the reaction.
Keywords: Glycolic acid; Glyoxal; hydrotalcite; kinetics